High-speed Internet access through unidirectional geostationary satellite channels. - Minei, I.
One of the proposed solutions for increasing the speed of Internet access is to connect the home user to a direct satellite channel, at a speed 20 times faster than that of an average telephone modem. Communication over satellite links is often characterized by sporadic high bit-error rates and burst losses. This is especially true when working in the Ka band, where weather conditions greatly affect link availability. Under such conditions, the TCP protocol that is predominantly used by data applications degrades dramatically in performance. Using simulations, this paper studies the performance of TCP under different network conditions. Several modifications, that take advantage of the special properties of the satellite channel, are proposed, and a new sender algorithm which can efficiently handle burst losses is presented. The main attractiveness of the proposed new sender algorithm is that it can be implemented only at the satellite ground station, rather than at every server in the world
Keywords: Ka band; TCP protocol; Burst losses; Data applications; Direct satellite channel; High bit-error rates; High-speed Internet access; Home user; Link availability; Network conditions; Satellite ground station; Satellite links; Sender algorithm; Simulations; Unidirectional geostationary satellite channels; Weather conditions